Corrigendum to “Competency of the Infantry Troops of the Nepalese Army in Disaster Response” - Malla, Shrijan; Hasegawa, Shuichi; Dahal, Ranjan (Journal of Risk Analysis and Crisis Response, 2021)
Corrigendum